2019
DOI: 10.24259/fs.v3i2.6005
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study on medicinal plants in traditional markets of Son La province, Vietnam

Abstract: Traditional markets in Vietnam are considered as important places for trading medicinal plants and also play a social role of exchanging traditional use of herbal medicine among different cultural and social groups at the local level. This study aims to identify and document medicinal plants used in 32 traditional markets of Son La province. Data were obtained through interviews and field observation method. A total of 167 informants include 13 herbalists, 49 herbal sellers, and 105 local people were interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 35 publications
10
36
0
4
Order By: Relevance
“…The dominant use of underground parts may be linked to the presence of bioactive compounds in these parts [102][103]. These results agree with the previous studies [25,64,65,78,92,[104][105][106][107][108][109]. Harvesting of the underground parts must be monitored at regular intervals for the sustainable use of the medicinal plant species [25,110].…”
Section: Diversity Of Medicinal Plant Species and Their Usessupporting
confidence: 84%
See 2 more Smart Citations
“…The dominant use of underground parts may be linked to the presence of bioactive compounds in these parts [102][103]. These results agree with the previous studies [25,64,65,78,92,[104][105][106][107][108][109]. Harvesting of the underground parts must be monitored at regular intervals for the sustainable use of the medicinal plant species [25,110].…”
Section: Diversity Of Medicinal Plant Species and Their Usessupporting
confidence: 84%
“…In some cases, honey, cow milk, chicken egg, rock sugar, salt, and mouse droppings were [76,87,102,106,107,117]. In the present study, oral administration was reported for the majority of remedies (63%), followed by topical administration (32%) and inhalation (5%) ( Table 4).…”
Section: Diversity Of Medicinal Plant Species and Their Usessupporting
confidence: 49%
See 1 more Smart Citation
“…The dominant use of underground parts may be linked to the presence of bioactive compounds in these parts [76][77][78]. These results agree with the previous studies [23,49,50,63,[79][80][81][82][83][84][85]. Harvesting of the underground parts must be monitored at regular intervals for the sustainable use of the medicinal plant species [23,86].…”
Section: Utilization Of Plant Partssupporting
confidence: 86%
“…Although surveys of wild edible plants and fungi sold in Southeast Asia are rare, some research effort has been put into studying the socioeconomic aspects of “green” open markets in general [ 44 – 47 ] as well as the contamination of plants with heavy metals [ 48 ] or parasites and pathogens [ 49 – 51 ]. Some studies from Southeast Asia performed in open air markets concern plant genetic resources from a single species, genus or family; the identification of the main cultivated plants (e.g., [ 52 – 56 ]); or medicinal plants [ 24 , 57 ].…”
Section: Introductionmentioning
confidence: 99%